Tofu Wastewater Treatment with the Growth Suspended Microorganism Using Different Air Flowrate - Novembrianto, Rizka; Hikmah Ayu M, Restu; Rosariawari, Firra (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2021)
This research discusses the processing of tofu wastewater with the aim of reducing and controlling the levels of pH, BOD, COD, TSS and temperature so as not to pollute the environment when dumped into rivers or other suitable places by simple reactors in few days. Water treatment process using bacterial from waste water as medium seems promising to develop since it does need any microorganism stater or other media like glucose. During the process of microorganism growth (seeding), the peak of MLSS was obtained on day 6 with 1560 mg/L. The other reason is wastewater from their wastewater processing is more suitable for microorganism cultivation because its effluent contains significant beneficial nutrienst and less of toxic compounds and harmful substances that interface with the growth of microorganism In same condition (pH and Temperature) in Acclimatization process can reach 77.45% after 7 days of treatment. After the detention time (18 hours) the results of COD number also greatly decrease with 5 hours recirculation with 8 L/min air flowrate and 86,51 % percentage of COD parameter decreased. This reseach is running in labolatory scale this problem must be recalculate to bring in large scale aplications, but this technology represents and effective, economilly and environmentally friendly process for tofu waste water treatment.